The Mediating Effect of KM Capabilities: Evidence from the Manufacturing and Technology Industries - Aman, Fadilah; Aitken, Ashley (Institute of electrical and Electronics Engineers Inc, 2010)
Based upon the theory of technology assimilation, information technology (IT) use for knowledge management (KM) is modeled to affect KM capabilities, which in turn affect KM effectiveness. A survey of 108 managers from manufacturing and technology industries indicates that IT support for KM had a significant positive relationship with KM capabilities and, in turn, affected the KM effectiveness. No significant direct relationship was detected between IT use for KM and KM effectiveness, indicating that KM capabilities variable is a full mediator. The results provide explanation for the lack of a direct link between IT use of KM and KM effectiveness and provides a potential framework for studies examining the impacts of other types of IT investments on KM effectiveness or success. The results also suggest that investments in IT use for KM must be carefully evaluated in terms of strategic directions to positively impact KM effectiveness as well as organisational performance.